ADSORPTION ISOTHERMS AND THERMOCHEMICAL DATA OF FD&C RED N° 40 BINDING BY CHITOSAN - Pinto, Luiz Antonio Almeida (2014)
Submitted by Taís Renata Pereira Amorim (tatahamorim_sjn@hotmail.com) on 2014-07-22T19:28:49Z No. of bitstreams: 1 31- ADSORPTION ISOTHERMS AND.pdf: 323365 bytes, checksum: 22bb08993a42739812231a85ca29c8b9 (MD5)